An optical tomography system using a digital signal processor - Ruzairi, Abdul Rahim; Chiam, Kok Thiam; Mohd Hafiz, Fazalul Rahiman (Molecular Diversity Preservation International (MDPI), 2009)
Link to publisher's homepage at http://www.mdpi.com